Implementation Of A Simplified Comprehensive Geriatric Assessment And Emergency Warning-Sign Education For Older Adults In An Internal Medicine Outpatient Clinic - Puji Setya Rini (Bhakti Sabha Nusantara, 2026)
Introduction: Older adults are vulnerable to acute health deterioration due to multimorbidity, functional decline, cognitive impairment, nutritional problems, and fall risk. Comprehensive Geriatric Assessment (CGA) provides a multidimensional approach to identifying geriatric problems and supporting appropriate interventions. This community service program aimed to implement simplified CGA and improve older adults’ knowledge of emergency warning signs. Methods: The program involved 30 older adults attending the Internal Medicine Outpatient Clinic of Muhammadiyah Hospital Palembang. Participants underwent simplified CGA covering medical, functional, cognitive and mental, fall-risk, nutritional, and social domains. Education on early recognition and initial management of emergency conditions was subsequently provided. Knowledge was assessed using pretest and posttest questionnaires. Data were analyzed descriptively and using the Wilcoxon Signed Rank Test. Results: Participants had a mean age of 68.77 ± 5.59 years, with equal proportions of males and females. The mean total CGA score was 12.20 ± 6.36. The highest mean scores were observed in the medical (3.67 ± 1.32), functional (3.03 ± 2.08), and fall-risk (1.93 ± 1.34) domains. The median knowledge score increased from 8.00 at pretest to 13.00 at posttest. All participants demonstrated increased scores, with a statistically significant difference between pretest and posttest results (Z = 4.835; p < 0.001). Discussion: Simplified CGA identified multidimensional geriatric problems, while targeted education was followed by improved knowledge of emergency warning signs. Conclusion: Integrating simplified CGA with emergency education is a practical approach to identifying geriatric problems and improving older adults’ immediate knowledge of emergency conditions.